Landslide risk management in Australia 2013 – status of resources available to practitioners - Leventhal, A.; Miner, A.; Walker, B. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Through its national committee, the Australian Geomechanics Society (AGS) has long recognised the contribution of Landslide Risk Management (LRM) to the wellbeing of the Australian community. As part of a commitment since 1985, the Society recently undertook two initiatives: the 2011 LRM ‘Risky Roadshow’ seminar series conducted throughout the nation; and in 2012 the development of an interactive ‘Education Empowerment’ website specifically directed towards LRM. The principle objective of these initiatives was to communicate and educate, and thereby empower, landslide practitioners and regulators with knowledge and tools required to implement best practice LRM, as well as to provide information to the general Australian populace regarding landslide risk. These educational resources and tools are based upon the internationally recognised LRM guidelines and commentaries published by AGS in 2000 and 2007. It was appropriate to build upon the guideline outcomes through these recent initiatives to benefit the Australian community. This paper provides background to the current status of LRM throughout the nation and provides advice on the package of resources available to assist practitioners in conducting landslide risk assessments.